Analisis Komparasi Algoritma Hash (Md5, SHA-2, SHA-3, SHA-512) Dan Teknik Salting Untuk Peningkatan Keamanan Data - Dini Febryana Sari; Athirah Media Sari; Inayatul Janah; Jefry Sunupurwa Asri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Data security has become a top priority with the increasing threat of cybercrime, such as password hacking and identity theft. One of the main ways to protect an information security data system is by using hash function-based cryptography. However, legacy hash algorithms such as MD5 and SHA-1 have proven vulnerable to various types of attacks. This study focuses on comparing the performance and security of MD5, SHA-2, SHA-3, and SHA-512 algorithms, as well as the effectiveness of using salting techniques. The method used is a comparative literature study of relevant previous research. The results of thekred analysis show that although MD5 excels in speed, this algorithm has a high vulnerability rate with an attack success rate of up to 35% on strong passwords. The SHA-3 algorithm shows the highest level of security with the lowest attack success rate of 20%, but has the slowest computation time. In contrast, with an average computation time of 512.8 ms, SHA-512 balances performance and security very well, especially when using JSON Web Tokens (JWT). This study concluded that the use of modern hash algorithms, such as SHA-512 or SHA-3, combined with salting techniques can significantly increase the resilience of a security system by up to 97.6%.